2021
DOI: 10.3389/fpsyt.2021.652717
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Healthcare Workers' Insomnia Symptoms and Fatigue in the Fight Against COVID-19, and the Role of Organizational Support

Abstract: Background: Healthcare workers (HCWs) have been exposed to increased risks of insomnia and fatigue during the COVID-19 pandemic. In this study, we identify important risk factors associated with insomnia symptoms and fatigue among HCWs, and evaluate the effect of organizational support on insomnia and fatigue symptoms.Methods: This is an online cross-sectional survey of HCWs in China administered during the COVID-19 epidemic (from February 27, 2020 to March 12, 2020). We employed the AIS-8 scale for insomnia s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 42 publications
4
27
0
3
Order By: Relevance
“…Although we found no studies involving nurses that used a similar scale to measure pandemic fatigue, a previous study of the general population showed similar findings (Labrague & Ballad, 2021). The results of the current study are in line with international studies (Zhan et al, 2020;Zou et al, 2021) that showed nurses who work directly with COVID-19 patients experience moderate-to-high levels of fatigue. Given the adverse consequences of fatigue, it is essential that institutional measures be in place to address this issue in nurses and promote their overall health and well-being.…”
Section: Ta B L E 3 Correlations Between Key Study Variablessupporting
confidence: 88%
See 2 more Smart Citations
“…Although we found no studies involving nurses that used a similar scale to measure pandemic fatigue, a previous study of the general population showed similar findings (Labrague & Ballad, 2021). The results of the current study are in line with international studies (Zhan et al, 2020;Zou et al, 2021) that showed nurses who work directly with COVID-19 patients experience moderate-to-high levels of fatigue. Given the adverse consequences of fatigue, it is essential that institutional measures be in place to address this issue in nurses and promote their overall health and well-being.…”
Section: Ta B L E 3 Correlations Between Key Study Variablessupporting
confidence: 88%
“…Consistent with earlier studies (Sagherian et al, 2020), our study found poorer mental health and reduced sleep quality in frontline nurses who experienced higher pandemic fatigue levels. Research involving health care workers including doctors, pharmacists and nursing assistants has also shown that fatigue associated with the pandemic may significantly affect sleep patterns and sleep quality (Teng et al, 2020;Zou et al, 2021).…”
Section: Ta B L E 3 Correlations Between Key Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both pathways of the study require approximately two to four hours to be completed, and participants will be asked to repeat the 50-question quiz after one month. There is currently a high level of fatigue amongst hospital staff related to the COVID-19 pandemic [38]. Even though the personnel and the different hierarchies express a high level of enthusiasm for this type of study, uncertainty remains regarding the number of participants who will engage in this study, and attrition might be high [39].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although some authors (Daumiller, Rinas, Hein, Janke, Dickhäuser, & Dresel, 2021 ; Kerres, 2020 ; Sokal, Trudel, & Babb, 2020 ) have noted the lack and importance of institutional support for educators during the COVID-19 transition to online learning, we identified a research gap, since the majority of studies have focused on organizational support during COVID-19 in the health sector (see Lethin et al, 2021 ; Morgantini et al, 2020 ; Zhang et al, 2020 ; Zou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%